FROM TOURISM GEOGRAPHY TO THE SPACE TOURISM ANALYSIS: THE TRACE IN COSTA RICA - Morera-Beita, Carlos Manuel (2016)
Tourism has been studied by geographers since the 19th century. At the beginning, this study was made from the corological perspective; however, it is from the middle of the 20th century that the tourism activity has been analyzed by using a systemic approach -with the Christaller, Butler, Vera, Hall and Page studies. This has created the fundamentals of current Tourism Geography, which deals with different aspects of tourism from a regional perspective as it has increased in the last century. This article reviews research conducted by geographers dedicated to researching tourism in Costa Rica, especially considering what has been published in the Revista Geográfica de América Central (Central American Geographical Journal), which is the main source to share the results of research made in this field of study in region. An inventory of the articles published in this journal –which cover this topic and analyze the perspective used, has been the methodology used in this article.